Parenting Stress in Mothers of Children With Autism Without Intellectual Disability. Mediation of Behavioral Problems and Coping Strategies - Miranda, Ana; Mira, Alvaro; Berenguer, Carmen; Rosello, Belen; Baixauli, Inmaculada (Frontiers in Psychology, 2019)
Parenting stress in mothers of children with autism without intellectual disability. Mediation of behavioral problems and coping strategies. Abstract The present study investigated the mediating role of behavioral difficulties, coping strategies, and social functional support in the relationship between ASD symptom severity and parenting stress in mothers of children with ASD. The parenting stress questionnaire, coping orientation to problems experienced scale, strengths and difficulties questionnaire, and Duke-UNC social support questionnaire were administered to 52 mothers, who also estimated the ASD severity symptoms of their children. Correlation analyses revealed that parenting stress was positively correlated with the children’s ASD symptoms and behavioral problems. On the other hand, parenting stress was negatively correlated with the engagement coping and social functional support reported by the mothers. Multiple mediation analysis indicated that engagement coping and behavioral difficulties were significant mediators in the relationship between ASD symptoms and parenting stress, with the engagement variable having a larger effect. The findings illustrate the need to promote the mothers’ engagement coping orientation and the application of behavioral strategies with their children to help them to buffer the impact of stress. Key words: Parental stress, social support, coping strategies, ASD, mediation analysis